The Kohistan between Gilgit and Chilas, northern Pakistan: regional tectonic implications - Khan, T.; Khan, M. A.; Jan, M. Q.; Latif, M. (Journal of Nepal Geological Society, 1996)
In this paper, we present geological description of an area located between Gilgit and Chilas within the Kohistan terrane. This terrane has been considered an intra-oceanic island arc, formed due to northward subduction of the Neo-tethyan lithospheric plate. At present, it is squeezed between the Karakoram Asian and Indian continental plates. Both the contacts are marked by suture zones, that is, Shyok (MKT) in the north and Indus (MMT) sutures in the south, respectively. The investigated area consists of plutonic, metamorphosed volcanic and sedimentary rocks, the Chilas Complex, and the Kamila Amphibolite. The metamorphosed volcanic and sedimentary rocks are packaged into the Jagfot Group. This group comprises basal turbiditic sediments, intercalated with amphibolites and calc-silicates (the Gilgit Formation), followed upward by the Gashu-Confluence Volcanics = Chait Volcanic Group, and finally the Thelichi Formation = Yasin Group of Aptian-Albian age. The Thelichi Formation comprises a volcanic base (Majne volcanics) and overlying turbidites, local intercalation of marbles, volcaniclastics and lava flows. Greenschist and amphibolite facies are common in the Jaglot Group, and particularly the sillimanite in the Gilgit Formation. A pair of anticline (the Gilgit anticline) and syncline (the Jaglot syncline) make up the structural scenario. On the basis of field geology, we conclude that the entire Jaglot Group and its equivalents, the Yasin Group, Chait Volcanic Group in Kohistan, and Burjila Formation, Bauma Harel Formation and Katzarah Formation in Ladakh show intra-oceanic back-arc basin rather than island arc affinities as suggested in the past.